A scoping review of the health effects of fermented foods in specific human populations and their potential role in precision nutrition: current knowledge and gaps - Humblot, Christèle; Alvanoudi, Panagiota; Alves, Emilia; Assunçao, Ricardo; Belovic, Miona; Bulmus-Tuccar, Tugce; Chassard, Christophe; Derrien, Muriel; Karagöz, Mustafa Fevzi; Karakaya, Sibel; Laranjo, Marta; Mantzouridou, Fani Th; et al. (Frontiers in Nutrition, 2025)
BackgroundDiets and specific foods have a significant impact on health, and individual responses to nutritional factors vary. This variability among humans can be considered a basis for developing personalized or precision nutrition. Fermented foods (FF) contain a wide range of macro- and micronutrients, bioactive compounds, and live or dead microorganisms. FF represent a diverse range of products and have garnered significant interest due to their potential health benefits. However, consistent evidence remains limited, possibly due to heterogeneity in individual responses.ObjectivesThe objective of this review is to assess and compile existing evidence on the variable responses of populations to FF and to determine whether FF could be integrated into a precision nutrition strategy.DesignInterventional and observational human studies were systematically collected. The publication identified the main factors likely to contribute to variable responses to FF across all health outcomes. The question was systematically addressed to assess the available evidence and identify knowledge gaps, guiding future research. A pragmatic approach was employed, following EFSA health claim guidelines, which require an assessment of food characteristics and mechanisms of action, as well as conducting a systematic search of human interventional studies. A similar approach was used to analyze data extracted from observational studies. The population included all humans (healthy and non-healthy, of all ages), encompassing both observational and interventional studies. The intervention consisted of the ingestion of any FF, while the control was defined as the absence or lower consumption of FF or consumption of a corresponding non-FF. Outcomes included all markers of the population's health status.ResultsThe main factors contributing to variable responses to FF across all health outcomes were related to initial phenotypic characteristics (biological sex, geographical origin, hormonal status, and age), baseline health status [metabolic syndrome [MetS], chronic metabolic pathologies, cancer, and psychological disorders], and genetic background. Additionally, since the gut microbiota is person-specific and influences metabolic responses, particular attention was paid to its functions and role in the variability of population responses to FF.ConclusionCollectively, this review represents a first step toward evaluating the feasibility of using FF in tailored nutritional strategies.Systematic review registrationhttps://osf.io/69d3f/overview.